Decrease of imperfection of GaAs epitaxial structures improvement of electrophysical and spectrometrical characteristics of silicon detectors under positron irradiation; Radiation effects express; Vol. 1, iss. 6 - Kuznetsov P. V.; Arefyev (Afef'ev, Arefiev) K. P. Konstantin Petrovich; Sokhoreva V. V.; Vorobiev S. A. (1988, 1988)
В фонде НТБ ТПУ отсутствует